THE EFFECT OF PRESSURE AND OPPORTUNITY IN DETECTING FINANCIAL STATEMENT FRAUDS IN CONSUMER GOODS INDUSTRY COMPANIES - Fani Irawati; Muchriana Muchran; Linda Arisanti Razak (Magister Akuntansi, Universitas Atma Jaya Makassar, 2023)
This study aims to determine the effect of pressure and opportunity in detecting fraud in the financial statements of companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange. This study uses quantitative data obtained from annual reports of companies that have been audited during the study period. The population of this study is the consumer goods industry with a population of 63 companies, using a porposive sampling technique, the number of companies that meet the sample criteria is 22 companies. The analysis technique used is multiple linear regression technique using the Common Model Effect (CEM) approach to panel data. The results of this study found that Financial Stability, Financial Target and Ineffective Monitoring had a positive and significant effect on the detection of fraud in the financial statements of companies in the consumer goods industry sector which were listed on the Indonesia Stock Exchange. Whereas External Pressure has a negative and insignificant effect on the detection of fraud in the financial statements of companies in the consumer goods industry sector that are listed on the Indonesia Stock Exchange.